Experimental study on the mechanical properties of loess containing tectonic joints - Wang, Huijuan; Zhang, Jinghua; Wang, Ping; Wang, Yali (Frontiers in Earth Science, 2025)
This study systematically examines the influence of joints on the mechanical properties of loess, highlighting the impact of joint dip angles on soil deformation and failure mechanisms. By employing an innovative layered compaction method to prepare jointed specimens, and conducting comparative experiments with different simulation materials (wax paper, rice paper, and plastic film), a series of controlled indoor triaxial compression tests were performed. The key findings are as follows: (1) The joint dip angle plays a decisive role in the evolution of failure mode, with five typical failure mechanisms identified based on fracture characteristics: shear failure, sliding failure, conjugate shear failure, sliding-shear failure, and sliding-conjugate shear failure. (2) The weakening effect of joints exhibits confining pressure dependency: Under low confining pressure (50 kPa), jointed specimens demonstrate increased axial displacement and a reduced shear strength attenuation ratio. (3) Mechanical parameters are significantly influenced by the dip angle: When the joint dip angle falls within the critical dip range of 60°–75°, both cohesion and internal friction angle reach their minimum values, forming zones of weakened mechanical properties. (4) A comparative analysis of simulation materials indicates that single-layer rice paper, due to its optimal thickness and tensile strength, effectively replicates the contact behavior of natural joint surfaces. This study establishes the quantitative relationship between joint geometric parameters and mechanical responses, providing an experimental basis for the engineering geological assessment of loess.